1985
DOI: 10.1007/bf02553907
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic correlations of operable carcinoma of the rectum

Abstract: Various histologic factors correlated to survival were studied in 124 patients radically operated on for rectal carcinoma in order to establish valid prognostic criteria. The total survival rate after five years was 63 percent, while in stage B1 it was 89 percent, in B2, 61 percent, and in C1, 47 percent (P less than 0.05). With regard to histotype, the survival was 83 percent in the papillary subtype of adenocarcinoma, while in the tubular subtype it was 62 percent, and 29 percent in the mucinous type (P = no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 8 publications
0
27
1
Order By: Relevance
“…Few papers have investigated the role of lymphocyte infiltration (Carlon et al, 1984;Svennevig et al, 1984;Jass, 1986;Harrison et al, 1994). In our study, no association was found between the presence of lymphocyte infiltration and clinical outcome, suggesting that the immunological response of the host to the primary tumour may not be related to metastatic potential, which is known to be the result of selected cell clones that have acquired the ability to deceive or overcome the host's immune strategies.…”
Section: Molecular and Cellular Pathologycontrasting
confidence: 56%
“…Few papers have investigated the role of lymphocyte infiltration (Carlon et al, 1984;Svennevig et al, 1984;Jass, 1986;Harrison et al, 1994). In our study, no association was found between the presence of lymphocyte infiltration and clinical outcome, suggesting that the immunological response of the host to the primary tumour may not be related to metastatic potential, which is known to be the result of selected cell clones that have acquired the ability to deceive or overcome the host's immune strategies.…”
Section: Molecular and Cellular Pathologycontrasting
confidence: 56%
“…Although some authors report that grade does indeed independently influence sur vival [1, 3,5, 11. 12, 17], there are numerous reports suggesting that grade is an unreliable prognostic variable [2,7,9,20], Of the pathologic parameters considered by Jass, lymphocytic infiltration was found to be the most important prognostic deter minant [6,7,15,16], The pattern of tumor growth had a lesser influence and tubule con figuration, the only parameter that is also routinely used to determine histologic grade [1, 3,6,7], had no influence on survival. Even though Jass et al [6] observed that the tubule configuration was significantly corre lated to survival in rectal cancer, this param eter was found to be an unreliable indicator of prognosis by the majority of authors [7,9,14].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an irregular, infiltrating pattern of growth, as opposed to a pushing 31, 34-36, 53, 56, 63, 78] and by univariate analysis in several additional studies [42,[79][80][81]. However, some border, has been demonstrated to be an adverse prog- 75 [42,56,84,85] and multivariate analyses [32,45,46,55,[87][88][89].…”
Section: Pathology Report In Colon Cancermentioning
confidence: 99%
“…However, other studies have either failed to confirm the prognostic significance of Currently, a large number of additional pathologic, biochemical, and molecular genetic parameters that may a peritumoral lymphoid reaction [32,89] or have demonstrated its significance only by univariate analysis have prognostic value in colorectal cancer are currently under investigation. Many will undoubtedly prove bio- [42,[92][93][94]. The results of these studies are difficult to com- Compton logically important, either as prognostic factors, as fac-to include additional categories is impractical given the mathematical model (i.e.…”
Section: Pathology Report In Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation